Effect of the Different Feed Formulas on Physiological Changes and Milk Production Performance of Holstein-friesian Crossbred Dairy Cows - Umpapol, Hanchai; Jitrajak, Tharadol; Songwicha, Choompol; Teanglum, Surachart; Sirikool, Watchara (Pakistan Journal of Nutrition, 2010)
The effect of 3 different feed formulas on some physiological changes, haematological changes, cortisol levels and milk production performance of Holstein-Friesian crossbred dairy cows were studied during the early period of the first lactation, by Randomized Complete Block Design with 4 replications and 3 treatments. Twelve cows were randomly assigned to each of the 3 feed formula groups as follows; (1) Commercial Feed as control group, (2) Cooperative-mixed Feed and (3) Cooperative-mixed Feed with the supplement of 2 kilograms of whole cottonseed/head/day. They were raised and managed in Sakon Nakhon Livestock Breeding and Research Station. The significant effects of feed formulas on physiological responses (rectal temperature, respiration rate, pulse rate and heat tolerance), haematological changes, cortisol levels and Average Daily Milk Yield (ADMY) were observed (p<0.05). The cows in group 3 showed higher Heat Tolerance Coefficient (HTC) than the cows in groups 1 and 2. The ADMY of cows in group 3 (7.89±0.62 kg/d) was higher than the cows in group 1 and 2 (7.72±0.32 and 7.70±0.64 kg/d), respectively. But milk composition was found only significant difference (p<0.05) in milk fat percentage.